Investigation of Original Honey Based on Electrical Impedance - Ronaldo Talapessy; Debora Fransiska Br. Giawa; Tomoaki Ikegami (Indonesian Journal of Applied Research (IJAR), 2023)
Honey comes from nectar extracted by bees and benefits the food industry. However, marketing often involves deception, such as mixing it with sugar. This study aims to distinguish between original honey and honey with adding sugar based on electrical impedance. The study was carried out to measure pure forest honey (Apis dorsata) and honey that was added sugar from 10 g to 60 g, where current 30 mA was applied at 100 Hz – 100 kHz. Additionally, some physicochemical characteristics of honey were measured to compare with the electrical impedance. The result shows that pure honey's impedance is lower than adding sugar. The electrical impedance of pure honey increases with the addition of sugar. Investigation of the electrical impedance on quality of honey preferable applied at the frequency from 100 Hz to 1 kHz.